MANAJEMEN METODE PELAKSANAAN PADA KONSTRUKSI BAJA MODEL “SPACE FRAME” PROYEK TERMINAL 3 ULTIMATE BANDAR SOEKARNO HATTA - Mochammad Rofiudin; Nawir Rasidi; Galih Damar Pandulu (Universitas Tribhuwana Tunggadewi Malang, 2017)
Commence a project ultimate terminal 3 Soekarno-Hatta airport Cengkareng, Jakarta, there are two important factors i.e. time factor and rescheduled work. This two factors are so need to be optimized by putting items together effectively, either before and after construction. Management system construction reference to the assumption that an implementation of the project can be implemented with the integrated system approach and the consistent of processes by the stage project implementation, if very stage process of system was done optimization against any problem. Time as one of main variables determine success or failure a project. The owners project expects net operation or the production of project have done. The sooner finished a project, the sooner ‘return of investment’ and the profit gained. The case that will be reviewed is an important of construction management system for handling a large project. From planning and control work time until they reached time of development projects effectively. Recommended to the community that construction management is one of alternative to reach particular purpose limited by time and resources. Understanding a construction project was an attempt to achieve a results in a building form desired and maximum profit.